Closed Toggle Pinning for Canine Traumatic Coxofemoral Luxation - Serdy, M. G.; Schulz, K. S.; Hornof, W.; Koehler, C.; Chiu, D.; Vasseur, P. B. (Veterinary and Comparative Orthopaedics and Traumatology, 1999)
A method of closed implantation of a toggle pin bone anchor and prosthetic ligament was developed for the treatment of traumatic canine coxofemoral luxation. Radiographic and anatomical evaluation of the canine femur and acetabulum were performed in order to develop an imaging and instrumentation technique that would allow closed placement of a toggle pin bone anchor under fluoroscopic guidance, while at the same time minimizing, or eliminating, damage to the articular cartilage. The surgical technique was then performed in 14 canine cadaver coxofemoral joints, followed by gross evaluation of implant placement, and potential cartilage or soft tissue damage. The cervical canal radiographic view of the proximal femur allowed placement of the drill hole through the fovea capitis of the femoral head without damaging the articular cartilage. The acetabular fossa was readily distinguishable from the acetabular articular cartilage on both of the lateral and ventrodorsal radiographic views of the pelvis. The toggle pin apparatus was inserted without damage to the articular cartilage in nine out of the fourteen hips and the bone tunnels were situated within the cancellous bone of the femoral neck in each of the nine specimens evaluated. Complications encountered during the procedure included bending and/or breakage of the guide wire in three hips and damage to the articular cartilage in two hips. The success of technique modifications designed to diminish the incidence of these complications awaits investigation in a clinical trial. Closed toggle pinning for canine traumatic coxofemoral luxation has the potential advantage of achieving rapid stabilization of the coxofemoral joint without damage to the articular cartilage and the need for an open approach to the joint. The clinical application of the technique is reported in one patient.The equipment and methodology for closed implantation of a toggle pin bone anchor and prosthetic ligament was developed for the treatment of traumatic coxofemoral luxation. A cadaver study was performed to assess the viability of the technique. Clinical application in one case is described.
Keywords: Coxofemoral; luxation; toggle pin; canine; fluoroscopic